Síndrome de Down versus alteração de linguagem : interação comunicativa entre pais e filhos - Mayer, Maria Grazia Guillen (2010)
The wish to express ourselves is vital and it comes from the efforts of human beings to satisfy physical and emotional needs. It is necessary to interact with other human beings in order to survive, find protection and stimulation and communication is born from this necessity. The process of communication involves several factors that can be observed and identified, although this process occurs in an unconscious, spontaneous, natural way. It might happen through linguistic codes (speaking, writing, gestural language) and non-linguistic codes (facial expressions, smiles, eye contact, touching and silences ) and it involves at least two people, classified as interlocutors, that exchange a message. The objective of the present study was to investigate the interaction between parents and their children with Down syndrome and parents and their children with language disorders. Five pairs of children with Down syndrome (DS) and their parents, and five pairs of children with language disorders and their parents took part in the research. First, an interview with the mothers containing data related to communication of the children was held. Moreover, three sections of recordings with each pair were made. The recordings occurred in previously prepared environments and with previously prepared material for the development of the activities. For the analysis of the interactions, two protocols were elaborated: Observation of the Verbal and Nonverbal Communicative Behaviors of the Adult towards the Child and Observation of the Verbal and Nonverbal Communicative Behaviors of the Child towards the Adult . The results showed that, in some aspects of interaction, mothers of children with language impairment show more suitable behavior during interaction with their children. The behaviors used by the mothers of children with language disorders and highlighted as the most positive ones, that is, the ones that help the process of language development, were: balance of the dialogical activity during interaction, suitable grammatical structure and speech complexity, more patience with the child and suitable intonation. However, mothers of children with Down syndrome showed more interest during communicative interaction. Related to the children, the ones with Down syndrome, when compared to the children with language disorders, showed more difficulty to understand rules and instructions provided by their mothers, expressed less interest in the activities, the discursive form was not adequate and the intonation was monotonous.